L'indice xérothermique: (Zur Frage der Klimaindizes) - Lauer, Wilhelm (ERDKUNDE, 1953)
Climatic indices (i. e. formulae which express the most important elements necessary for the characterization of the climate at a given place) make possible the cartographic representation of the zoning and gradation of arid and humid types of climate. Annual means give unsatisfactory results but by the use of monthly means it is possible to arrive at the number of humid and arid months respectively which in the tropics and subtropics are closely related to the belts of vegetation. A further refinement of the method of climatic indices is made possible by the determination of the number of „trockene Tage (drought days). In order to determine the „trockene Tage the Indice xérothermique (after Gaussen and Bagnouls) is used whidi is based on precipitation, temperature, relative humidity and considers even fog and dew. It is important to take great care in the selection of the day of the month from which the „trockene Monate (drought months) begin since they fix the period within which (according to Gaussen and Bagnouls) the „trockene Tage have to be counted. Bad selection in fixing these months would lead to less valuable results. — Climatic indices cannot serve as a substitute for climatic classification but they are a useful criterion of the distribution of humidity and aridity within a climatic zone.